University Students’ Perceptions of Extensive Reading Intervention: Evidence from Universitas Hasanuddin Non-English Freshmen - Pammu, Abidin; Dewintha, Rezza; Nursafira, Mutia Sari (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
This paper reports the findings drawn from a six-month survey on first-year students’ perception of Extensive Reading intervention in a basic general English course program at Hasanuddin University. This survey study aimed to reveal the extent to which the samples agreed on some aspects of language learning’s positive impacts from attending a reading intervention semester. Other aspects were also examined to the degree of improvement, such as students’ beliefs about eclecticism, self-confidence, and social identity. Data were obtained from questionnaire surveys consisting of 7 close-ended statements and four rating scales from 120 fresh undergraduates. The scaling of “strongly agreement” was tallied from the total samples to obtain the trend. The greater the percentage of the agreement rate, the stronger the perceptions, so as the higher the tendency of the positive impact of extensive reading. The findings came up with encouraging results where a greater proportion of the samples reported significant improvement in aspects contributing to language learning. These include improved vocabulary, writing skills, reading rate, comprehension, confidence, and motivation. The study also revealed the perceived gaining of social identity and reduced degree of eclecticism in dealing with English texts. The findings support the previous research that confirms assurance of reading improvement through extensive reading. The survey warrants pedagogical implications for teachers to constantly embark high intensity of reading activities for students to inculcate reading habits so as to improve personal study skills and encourage autonomous learning.